Harpacticoid copepods—their symbiotic associations and biogenic substrata: a review - Huys, Rony (Zootaxa, 2016)
Members of the order Harpacticoida are primarily free-living and benthic but some lineages have adopted alternative modes of life which involve a major habitat shift or dependence on a host. Since the first discovery of a harpacticoid associated with an invertebrate host about 150 years ago, a total of 172 species, representing 84 genera and 17 families, have been shown to live in symbiotic partnership with other organisms. The steady addition of new taxa during the last 35 years testifies to the widespread and previously underestimated occurrence of symbiosis in the group. Harpacticoids have entered into associations with Cyanobacteria, Protozoa, macroalgae, grasses, fish hosts, marine tetrapods (including whales, sea turtles and manatees) and at least eleven invertebrate phyla. At present, 86 independent colonizations of marine and freshwater host organisms can be identified but this number is a minimum estimate and is expected to increase as certain host groups will be more properly sampled. In contrast to the Cyclopoida and Siphonostomatoida, which have been extremely successful in developing associations with cnidarians, sponges, echinoderms and ascidiaceans, members of the Harpacticoida have a marked predilection for crustacean hosts. Except for a few species that can be classified as genuine parasites, the precise nature of the relationship between most associated harpacticoids and their hosts has yet to be elucidated but can probably be defined as commensalistic, where the benefit to the copepod may be nutritional or protective. Most are ectosymbiotic but some live as endocommensals in microhabitats which provide considerable protection from predation. The success of symbiotic harpacticoids in freshwater is limited with the few species known to be associated with freshwater hosts typically representing isolated forays into a symbiotic lifestyle from an otherwise free-living lineage. The scattered literature on symbiotic harpacticoids is compiled and presented by host group. Dichotomous keys are provided for the identification of most species while accidental and doubtful records are discussed where appropriate. The genus Idomenella T. Scott, 1906a (Pseudotachidiidae), previously a junior subjective synonym of Dactylopodella Sars, 1905a, is reinstated to accommodate Dactylopodella rostrata (T. Scott, 1893), D. janetae Hicks, 1989, Xouthous coronatus (T. Scott, 1894b), X. antarcticus (Giesbrecht, 1902), X. intermedius (Lang, 1934) and Idomenella paracoronata sp. nov. Kioloaria Harris, 1994 (Porcellidiidae) is adopted as the valid replacement name for the preoccupied Acutiramus Harris, 2014a. The name of a second porcellidiid genus, Murramia Harris, 1994, lacks the mandatory type fixation and is made available here by adopting the original name but taking the present authorship and date. The generic name Ellucana Sewell, 1940 is currently unavailable and must instead be attributed to Coull (1971b). Laophonte commensalis Raibaut, 1962a is fixed as the type of Raibautius gen. nov. in the family Laophontidae, Tegastes cnidicus Humes, 1981b as the type of Aglaogastes gen. nov. in the Tegastidae, and Canuella (Canuella) indica Krishnaswamy, 1957 as the type of Indicanuella gen. nov. A number of new names are proposed for species that had previously been misidentified: Diarthrodes septemtrionalis sp. nov. for D. roscoffensis (Monard, 1935b) sensu Kornev & Chertoprud (2008), Kioloaria jejuensis sp. nov. for Porcellidium brevicaudatum Thompson & Scott, 1903 sensu Kim & Kim (1996), Xouthous andamanensis sp. nov. for X. maldivae [sic] Sewell, 1940 sensu Wells & Rao (1987), X. wellsi sp. nov. for X. laticaudatus (Thompson & Scott, 1903) sensu Wells (1967), X. namibiensis sp. nov. for X. pectinatus (Scott & Scott, 1898) sensu Kunz (1963), and Idomenella paracoronata sp. nov. for Idomene coronata (T. Scott, 1894b) sensu Sars (1909a). The inadequately described Amenophia ovalis Brady, 1910 is relegated to a species inquirenda in Amenophia Boeck, 1865. Idomene australis Brady, 1910, I. pusilla Brady, 1910, Dactylopusia ferrieri T. Scott, 1912 and I. kabylica Monard, 1936 are ranked species incertae sedis in the Pseudotachidiidae. Dactylopus bahamensis Edwards, 1891 is tentatively considered as species incertae sedis in the Dactylopusiidae. Canuellina onchophora Por, 1967 and C. nicobaris Wells & Rao, 1987 are transferred to the genus Ellucana Coull, 1971b while Ellucana secunda Coull, 1971b is assigned to the genus Canuellina Gurney, 1927. Xylora calyptogenae Willen, 2006 is sunk as a junior subjective synonym of X. bathyalis Hicks, 1988a. The incorrect original spellings of Parathalestris pacificus Chislenko, 1971, P. infestus Ho & Hong, 1988, Tripartisoma ovalis Avdeev, 1983, T. trapezoidalis Avdeev, 1983, Amplipedicola pectinatus Avdeev, 2010 and Sunaristes japonicus Ho, 1986a are amended to reflect agreement in gender with their respective generic names.